2022
DOI: 10.3934/microbiol.2022038
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study on the binding affinity of SARS-CoV-2 spike protein to antibodies

Abstract: <abstract> <p>The COVID-19 pandemic has caused a worldwide health crisis and economic recession. Effective prevention and treatment methods are urgently required to control the pandemic. However, the emergence of novel SARS-CoV-2 variants challenges the effectiveness of currently available vaccines and therapeutic antibodies. In this study, through the assessment of binding free energies, we analyzed the mutational effects on the binding affinity of the coronavirus spike protein to neutralizing ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…This result aligned with previous studies that described considerably reduced humoral responses against the Omicron strain and almost no vaccine effectiveness against symptomatic disease after two doses of BNT162b2 [39]. Omicron sub-variants have generally higher immune escape ability than other SARS-CoV-2 VOCs [35,40], even though the earlier Omicron sub-variants (BA.1 and BA.2) appeared to have stronger binding affinities than other VOCs [40]. The Omicron variant is characterized by great antigenic variability due to the selection of 37 mutations in the spike protein, the main immunogenic protein of the virus, and it is capable of inducing the production of neutralizing antibodies [41,42].…”
Section: Discussionsupporting
confidence: 91%
“…This result aligned with previous studies that described considerably reduced humoral responses against the Omicron strain and almost no vaccine effectiveness against symptomatic disease after two doses of BNT162b2 [39]. Omicron sub-variants have generally higher immune escape ability than other SARS-CoV-2 VOCs [35,40], even though the earlier Omicron sub-variants (BA.1 and BA.2) appeared to have stronger binding affinities than other VOCs [40]. The Omicron variant is characterized by great antigenic variability due to the selection of 37 mutations in the spike protein, the main immunogenic protein of the virus, and it is capable of inducing the production of neutralizing antibodies [41,42].…”
Section: Discussionsupporting
confidence: 91%
“…The ΔΔ G of BA.3 to antibodies CT‐P59, AZD1061, and LY‐CoV555 is more positive than that of BA.1 (Table S3), indicating greater interference with the spike/antibody interactions and possible stronger immune evasion. BA.4 exhibits a stronger spike/antibody affinity reduction effect than the other three sublineages (Table S3) implying it may have the strongest immune evasion ability 77 . These analyses suggested that, in addition to gaining strong ACE2 affinity, the omicron variant has larger immune evasion ability to further enhance its transmission ability.…”
Section: Resultsmentioning
confidence: 92%
“…BA.4 exhibits a stronger spike/antibody affinity reduction effect than the other three sublineages (Table S3) implying it may have the strongest immune evasion ability. 77 These analyses suggested that, in addition to gaining strong ACE2 affinity, the omicron variant has larger immune evasion ability to further enhance its transmission ability.…”
Section: Weaker Affinities To Most Antibodiesmentioning
confidence: 99%
“…This CG model is designed to characterize protein stabilities and conformational energies, which also enhances the model’s electrostatic properties ( 31 ), and has been refined specially for the analysis of membrane protein ( 32 ). Furthermore, the CG model has been extensively employed to investigate the molecular mechanism of biological functions in a broad array of complex systems, like ATPase ( 33 35 ), GPCRs ( 36 38 ), Hv1 channel ( 39 ), and SARS-Cov2 spike protein ( 40 43 ). Its extensive application has affirmed it as a reliable tool to depict the energy landscapes during the conformational transitions of proteins.…”
mentioning
confidence: 99%